Inferior pancreaticoduodenal artery aneurysm associated with obstruction of the celiac trunk and cancer of the head of the pancreas - Ćulum Jovan; Golić Darko; Guzijan Aleksandar; Jović Darko; Jakovljević Branislava; Jakovljević Aleksandar; Grahovac Davor (Scripta Medica, 2015)
Aneurysm of the visceral arteries is a rare condition and it represents around 1% of all arterial aneurisms. Aneurysm of the inferior pancreaticoduodenal artery represents around 2% of all visceral aneurysms. Aneurysm associated with occlusion of the coeliac trunk is very rare condition and there are only about 40 cases presented in the literature. In our study, we presented 56 year-old female admitted to hospital with obstructive jaundice. CT scan diagnosed tumor of the head of pancreas and CT angiography confirmed aneurysm of the inferior pancreaticoduodenal artery which was successfully operated at our clinic.